Effects of Entrepreneurship Training, Digital Innovation, and Social Capital on Business Sustainability in the Creative Industry Sector - Judijanto, Loso; Ode, Haruni; Rukmana, Arief Yanto; Antoni, Antoni; Thalib, Najdah (West Science Journal Economic and Entrepreneurship, 2024)
This study investigates the impact of Digital Innovation, Entrepreneurship Training, and Social Capital on Business Sustainability within the creative industries sector. Utilizing a quantitative research approach, data were collected from 150 business owners and managers using a structured questionnaire with a five-point Likert scale. The data were analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS 3) to test the proposed hypotheses. The results reveal that all three factors—Digital Innovation, Entrepreneurship Training, and Social Capital—have positive and significant effects on Business Sustainability. Specifically, Social Capital emerged as the strongest predictor, followed by Digital Innovation and Entrepreneurship Training. These findings underscore the importance of embracing digital technologies, investing in entrepreneurial education, and cultivating strong social networks to enhance the sustainability of creative enterprises. The study provides valuable insights for practitioners, policymakers, and educators in the creative industries, offering practical strategies for fostering long-term business success.